1.6k views
0 votes
If you were to use the substitution method to solve the following system, choose the new equation after the expression equivalent to x from the first equation is substituted into the second equation. x + 4y = −9 2x + 5y = −6 (6 points) Question 2 options: 1) 2x + 5(4y − 9) = −6 2) 2x + 5(−4y − 9) = −6 3) 2(4y − 9) + 5y = −6 4) 2(−4y − 9) + 5y = −6

User Kmoe
by
4.3k points

2 Answers

3 votes

Answer: 1) Solve for x in the first equation: x = -6y+29

2) –6x + 29

3) Simplify and solve for the variable that remains: y = 4

4) Back substitute y = 4 and solve: x=5

4)Therefore, the solution is (x, y) = 5,4

5) x + 6y = 29 (5,4)

2x - 4y = -6 (5,4)

Step-by-step explanation: just did the assignment

User Helenesh
by
4.6k points
4 votes

Answer:

2(−4y − 9) + 5y = −6

Explanation:

Just completed the Test

User Justin Rusbatch
by
4.6k points